What influences informal caregivers' risk perceptions and responses to home care safety of older adults with disabilities: A qualitative study - Cao, Songmei; Huang, Huanhuan; Bo, Suping; Feng, Man; Liang, Yiqing; Liu, Yuqing; Zhao, Qinghua (Frontiers in Public Health, 2022)
Objective: This study aimed to explore the factors that influence risk perceptions and responses by informal caregivers of older adults with disabilities. Methods: A descriptive qualitative study was performed, and the socio-ecological framework was applied to interpret the complex influences on individual risk perceptions and responses. Semistructured interviews were conducted with sixteen informal caregivers of older adults with disabilities. The interviews were transcribed verbatim and analysed using content analysis. Results: The four levels of the socio-ecological framework successfully allowed for the analysis of influences on the risk perceptions and responses of informal caregivers as follows: at the individual level: previous experiences, personality characteristics, health literacy, and care burden; at the familial level: economic status, emotional connection, informational and decisional support; at the community level: health service accessibility and neighbour communication; and at the social level: responsibility-driven culture, media advocacy, and ageing policies. Conclusions: The establishment of risk perceptions and coping behaviours by informal caregivers was affected by many factors. Using the framework to interpret our findings provided insight into the influence of these varying factors. Comprehensive, realistic, and achievable strategies are needed for improving the risk perceptions of informal caregivers in home care by addressing personal, familial, and social environmental factors.